As an End to Conflict Amplification - Franzen, Aaron B. (Christian scholar's review, 2025)
Aaron B. Franzen When I look into the face of my enemy I see my brother, I see my brother Forgiveness is the garment of our courage The power to make the peace we long to know Open up our eyes To see the wounds that bind all of humankind May our shutter hearts Greet the...